Mirror neuron activation in children with developmental coordination disorder: A functional MRI study. Issue 47 (December 2015) - Reynolds, Jess E.; Licari, Melissa K.; Billington, Jac; Chen, Yihui; Aziz-Zadeh, Lisa; Werner, Julie; Winsor, Anne M.; Bynevelt, Michael
Highlights: Decreased activation in mirror neuron regions in DCD during action observation. Deactivation of the pars opercularis during imitation in DCD group. Further research to explore mirror neuron function in DCD is needed. Abstract: The aim of this study was to reveal cortical areas that may contribute to the movement difficulties seen in children with Developmental Coordination Disorder (DCD). Specifically, we hypothesized that there may be a deficit in the mirror neuron system (MNS), a neural system that responds to both performed and observed actions. Using functional MRI, 14 boys with DCD ( x ¯  = 10.08 years ± 1.31, range = 7.83 − 11.58 years) and 12 typically developing controls ( x ¯  = 10.10 years ± 1.15, range = 8.33–12.00 years) were scanned observing, executing and imitating a finger sequencing task using their right hand. Cortical activations of mirror neuron regions, including posterior inferior frontal gyrus (IFG), ventral premotor cortex, anterior inferior parietal lobule and superior temporal sulcus were examined. Children with DCD had decreased cortical activation mirror neuron related regions, including the precentral gyrus and IFG, as well as in the posterior cingulate and precuneus complex when observing the sequencing task. Region of interest analysis revealed lower activation in the pars opercularis, a primary MNS region, during imitation in the DCD group compared to controls. These findings provide some preliminary evidence to support a possible MNS dysfunction in children with DCD.